2010
DOI: 10.1021/es903221p
|View full text |Cite
|
Sign up to set email alerts
|

Virus’ (MS2, ϕX174, and Aichi) Attachment on Sand Measured by Atomic Force Microscopy and Their Transport through Sand Columns

Abstract: Atomic force microscopy (AFM) was used to study the attachment of phiX174, MS2, and Aichi viruses on sands of different surface properties: oxide-removed (clean), goethite-coated, and aluminum oxide-coated. Interaction forces between viruses and sand surfaces were measured by contact mode AFM using tips coated with particles of each virus. Column experiments were conducted to quantify the macroscopic transport and retention of the viruses in sand. The average adhesion force measured with AFM was highest betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 53 publications
8
68
0
Order By: Relevance
“…The plant growth medium has been shown to play the most significant role in pathogen internalization via uptake by the root system (51). The factors that contribute the most significantly to viral transport in the soil include the soil type, water saturation, pH, conductivity, and organic matter (58,59). Based on the variability that soil growth medium adds to pathogen internalization, the detection of virus internalization and dissemination in fresh produce grown in soil has been less well established than in hydroponic systems (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant growth medium has been shown to play the most significant role in pathogen internalization via uptake by the root system (51). The factors that contribute the most significantly to viral transport in the soil include the soil type, water saturation, pH, conductivity, and organic matter (58,59). Based on the variability that soil growth medium adds to pathogen internalization, the detection of virus internalization and dissemination in fresh produce grown in soil has been less well established than in hydroponic systems (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the virus may adhere to positively charged materials found in the soil and be tightly bound in the soil matrix. In terms of soil, pH 6.1 to 6.5 is considered slightly acidic, and pH 6.6 to 7.3 is considered neutral (58,59). Under drought conditions, the soil pH was 6.4 with TV and 6.3 with MNV-1, which may account for the decrease in viral dissemination for TV, since the virus was bound to soil.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they are nonpathogenic to human, specific to host bacteria, simple to assay, and have good survival characteristics (Cao et al 2010). However, relatively less attention has been given to pathogenic viruses (Pancorbo et al 1988;Quanrud et al 2003;Attinti et al 2010), and specifically to adenoviruses as indicator viruses (Davies et al 2006;Horswell et al 2010;Wong et al 2012Wong et al , 2014. Fluorescent polystyrene nanospheres (FPNS) have also been used as virus surrogates in studies of virus transport in porous media, where 70-nm sized silica nanoparticles were covalently coupled with specific proteins and a DNA marker for sensitive detection (Pang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DLVO theory thus fails to explain why retention of HAdV was much higher than MS2 at 1 and 10 mM. The hydrophobic interaction is not accounted for here since previous studies have shown hydrophobic interaction between sand and HAdV/MS2 is not significant [14,16]; however, hydrophobic interaction should be considered if the future studies are conducted in clay colloids [36].…”
Section: Distance (Nm)mentioning
confidence: 95%
“…Due to its prevalence in environmental waters, HAdV is a promising fecal source tracker [7] and has been included in the U.S. Environmental Protection Agency's contaminant candidate lists one, two and three in 1998, 2005 and 2007, respectively [8]. Most viral transport studies, however, focus on bacteriophages [9][10][11][12][13], with MS2 being the most common [5,[9][10][11][13][14][15]. For the first time, a sorption isotherm approach to evaluate the influence of ion composition and organic carbon on the sorption behavior of HAdV to soil and sand particles [16,17] was utilized by our research group.…”
Section: Introductionmentioning
confidence: 99%